Influência do meio de cultivo e do silício na fisiologia e anatomia de Bromelia antiacantha (Bromeliaceae) - Cipriano, Rosiane (2016)
The Plant Tissue Culture may contribute to the proliferation of various species of commercial interest, and has gained ground in the preservation of rare or endangered species, such as bromeliads. To perform these techniques, nutrient medium, that provide substances essential for growth and development in vitro of plants are utilized. However, the growing conditions can lead to the formation of plants with structures and tissues undeveloped, anatomically or physiologically, which may affect subsequent establishment ex vitro. In order to find a better concentration of MS medium (MURASHIGE; SKOOG, 1962) over and influence of silicon in vitro and ex vitro culture of B. antiacantha it was held two jobs. The first (Chapter II) aimed to define a culture medium for the in vitro establishment of B. antiacantha testing different concentrations of complete MS medium (0, 25%, 50%, 75% and 100%) on seed germination and in vitro growth of this bromeliads and the photosynthetic efficiency of plants established under these conditions. The second (Chapter III) aimed to evaluate the effect of different sodium silicate concentrations (Na2SiO3) (0, 2,5, 5,0, 10 and 15 mg L-1) growth and physiology in vitro and ex vitro and anatomy ex vitro of B. antiacantha. In the first study the experimental design was completely randomized (DIC) consisting of 13 replicates per treatment (each replicate contained four seeds per bottle). Germination was evaluated daily to determine the germination speed index (GSI), the average germination time (GMT) and at the end of 90 days were evaluated germination percentage (G%), the number of leaves (NF ) and roots (NR), the air length (CA) and root (CR), leaf area (AF), the fresh weight of seedling (MFP) and also the measurements of chlorophyll a fluorescence. In the second experiment the experiment in DIC consisting of 5 replicates per treatment (each repetition contained 5 tubes, with one plant per tube). Elapsed 45 days in vitro cultivation were evaluated growth parameters (NC, NR, CA, CR, AF and MFP) and also the fluorescence measurements of chlorophyll. After 28 days of cultivation ex vitro were evaluated the same growth parameters and taken leaf samples to evaluate the thickness of adaxial and abaxial epidermis, the chlorenchyma, the hydrenchyma and estimate the number of stomata. Fluorescence measurements of chlorophyll were carried out at 7, 14, 21 and 28 days of acclimatization. Data were submitted to analysis of variance (ANOVA) and the means were compared by Tukey test (p ≤ 0.05). It appears that for the species B. antiacantha, medium MS 25% promoted the best results for germination, growth and development of the photosynthetic apparatus of plants. The use of Na2SiO3 only influenced parameters AF during in vitro cultivation and CA during the ex vitro cultivation. In relation to the photosynthetic apparatus, the JIP parameters showed photoinhibition effect at 7 and 14 days and at the concentrations of 5 and 10 mg L-1 Na2SiO3. Thus, it can be inferred that Na2SiO3 not acted improving the functioning of the photosynthetic apparatus, since other silicate concentrations (2,5 and 15 mg L -1) did not differ significantly between 5 and 10 mg L -1 . B. antiacantha present tetracytic stomata with hypostomatic distribution, had a layer of epidermal cells on both sides of the sheet, water storage parenchyma (hydrenchyma) with thin cell walls on the side of the adaxial surface, chlorophyll parenchyma (chlorenchyma) cells with isodiametrical, collateral vascular bundles, usually larger beams alternated with the minor. The mesophyll has a dorsiventral organization. The leaf anatomy of the concentration of 2,5 mg L-1 and 15 mg L-1 Na2SiO3 promoted beneficial effects on seedling through the increased stomatal density and thickness of adaxial epidermal respectively.